Mechanics and electrodynamics of magneto-and electro-elastic materials - Ogden, R. W. 1943-; Steigmann, David J. (CISM courses and lectures, 2011)
This volume presents a state-of-the-art overview of the continuum theory of both electro- and magneto-sensitive elastomers and polymers, which includes mathematical and computational apsects of the modelling of these materials from the point of view of material properties and, in particular, the "smart-material" control of their mechanical properties.